Well-being among social entrepreneurs in Malaysia: a theoretical domains framework - Sahharon, Hamizah; Abdullah, Haslinda; Alby, Jeffrey Lawrence D'Silva; Ahmad, Aminah; Ismail, Ismi Arif (Universiti Putra Malaysia Press, 2019)
The term Social Entrepreneurship (SE) is not new in Malaysia but not many studies were done on this community, especially on their subjective well-being. This term has long been debated among scholars because it is a fast-growing phenomenon among both academics and practitioners in the area. SE is defined as an entrepreneurial activity known to address basic human needs such as giving access to basic education, employment, health aid, community development, and socio-economic empowerment. It differs from commercial entrepreneurship because SE focuses on social strategies and values because they believe in the importance of creating social changes, which has the potential payoff and transformational benefits to those involved whether in providing or receiving the services. Such impact is reflected on social entrepreneur's satisfaction, happiness, meaningfulness of life, social connectedness and health. However, the limited research on well-being in Malaysia relies on measures that simply assess an individual's satisfaction with specific aspects of life such as housing and income. Therefore, these measures are not appropriate to assess the positive impact of SE on social entrepreneur's well-being. Thus, after meticulous reviews of literature through Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA), an insight on the number of records were identified through the applied search engines. As a result, the search stratagem came out with a framework of well-being measures that take into account behavioural, cognitive intentions, motivational choices, feeling and functioning of social entrepreneurs. After a full text review, about seven articles were included yielding four identified domains associated to well-being and social entrepreneurs.